KOMPETENSI DOSEN PRODI PAI FAKULTAS TARBIYAH DAN KEGURUAN UIN ANTASARI BANJARMASIN - Samdani Samdani; Isny Lellya (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Educators, whether teachers, lecturers or whatever their names are, are one of the factors that carry out the task of guiding, encouraging and developing the potential of students towards perfection, therefore the role of educators is very significant for the achievement of a system in education. Lecturers as professionals and scientists have the main task of transforming, developing and expanding science, technology and art through education, research and community service. Professional lecturers are an important component in the education system at tertiary institutions, they have the roles, duties and responsibilities needed to assist the government in realizing national education goals, namely to improve the quality of Indonesian people, both in faith, noble character, mastery of knowledge, arts and technology to realize the creation of a prosperous, advanced, just and civilized Indonesian society. These tasks certainly require the competence of a mature educator so that they can achieve the objectives of the study program in which the lecturer is assigned.